MECHANISMS OF ORGANIZING GASTRONOMY TOURISM SERVICES AND ITS DEVELOPMENT (American Journal of Business Management, Economics and Banking, 2024)
Tourists, in particular, are interested in gastronomic tourism experiences after being happy with the site and local cuisine, resulting in destination loyalty. Increased usage of local cuisine in the region's tourism economy strengthens the area's tourism offering while also potentially contributing to the district’s tourism growth. The study’s major focus is on the mechanisms of organizing gastro-tourism services and their development in Uzbekistan.